Conjugated Linoleic Acid Prevents Ovariectomy‐Induced Bone Loss in Mice by Modulating Both Osteoclastogenesis and Osteoblastogenesis. Issue 3 (13th December 2013) - Rahman, Md Mizanur; Fernandes, Gabriel; Williams, Paul
Abstract: Postmenopausal osteoporosis due to estrogen deficiency is associated with severe morbidity and mortality. Beneficial effects of conjugated linoleic acid (CLA) on bone mineral density (BMD) have been reported in mice, rats and humans, but the effect of long term CLA supplementation against ovariectomy‐induced bone loss in mice and the mechanisms underlying this effect have not been studied yet. Eight‐week old ovariectomized (Ovx) and sham operated C57BL/6 mice were fed either a diet containing 0.5 % safflower oil (SFO) or 0.5 % CLA for 24 weeks to examine BMD, bone turn over markers and osteotropic factors. Bone marrow (BM) cells were cultured to determine the effect on inflammation, osteoclastogenesis, and osteoblastogenesis. SFO/Ovx mice had significantly lower femoral, tibial and lumbar BMD compared to SFO/Sham mice; whereas, no difference was found between CLA/Ovx and CLA/Sham mice. CLA inhibited bone resorption markers whereas enhanced bone formation markers in Ovx mice as compared to SFO‐fed mice. Reverse transcriptase polymerase chain reaction and fluorescence activated cell sorting analyses of splenocytes revealed that CLA inhibited pro‐osteoclastogenic receptor activator of NF‐κB (RANKL) and stimulated decoy receptor of RANKL, osteoprotegerin expression. CLA also inhibited pro‐inflammatory cytokine and enhanced anti‐inflammatory cytokine production of lipopolysaccharide‐stimulated splenocytes and BM cells. Furthermore, CLA inhibited osteoclast differentiation in BM and stimulated osteoblast differentiation in BM stromal cells as confirmed by tartrate resistant acid phosphatase and Alizarin Red staining, respectively. In conclusion, CLA may prevent postmenopausal bone loss not only by inhibiting excessive bone resorption due to estrogen deficiency but also by stimulating new bone formation. CLA might be a potential alternative therapy against osteoporotic bone loss.